Preparation of Silk Sericin/Lignin Blend Beads for the Removal of Hexavalent Chromium Ions - Hyo Won Kwak (International Journal of Molecular Sciences, 2016)
In the present study, novel adsorbents having high adsorption capability and reusability were prepared using agricultural by-products: silk sericin and lignin. Silk sericin and lignin blend beads were successfully prepared using simple coagulation methods for the removal of hexavalent chromium (Cr(VI)) from aqueous solution. A 1 M lithium chloride (LiCl)/dimethyl sulfoxide (DMSO) solvent system successfully dissolved both sericin and lignin and had sufficient viscosity for bead preparation. Compared to the conventional sericin bead adsorbent, sericin/lignin blend beads showed higher Cr(VI) adsorption capacity. The amount of lignin added to the adsorbent greatly affected the adsorption capacity of the beads, and a 50:50 sericin/lignin blend ratio was optimal. Adsorption behavior followed the Freundlich isotherm, which means the adsorption of Cr(VI) occurred on the heterogeneous surface. Cr(VI) adsorption capability increased with temperature because of thermodynamic-kinetic effects. In addition, over 90% of Cr(VI) ions were recovered from the Cr(VI) adsorbed sericin/lignin beads in a 1 M NaOH solution. The adsorption-desorption recycling process was stable for more than seven cycles, and the recycling efficiency was 82%. It is expected that the sericin/lignin beads could be successfully applied in wastewater remediation especially for hazardous Cr(VI) ions in industrial wastewater.